PENGARUH BOOK TAX DIFFERENCE TERHADAP RELEVANSI NILAI INFORMASI LABA - Pratana Puspa Midiastuty; Eddy Suranta; Lidya Ofprama Dita (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
This research aims to test the book-tax difference towards the value relevance of earning information presented by the company. The value relevance of earning information in this study measured using market value equity proxy. This study classifies the sample of firms into a High ETR group and Low ETR groups based on the calculation of effective tax rate (ETR). The sample of this research is 85 manufacturing companies listed on the Indonesia stock exchange in 2015-2018. The Method of data collecting was using a purposive sampling technique. The data using ANOVA Test-Compare to find out whether there is a difference between the book-tax difference at companies that include High ETR and Low ETR, and multiple linear analysis using SPSS software find out whether companies with the large book-tax difference and included a group of Low ETR has the informational value relevance of earnings is low. The result showed that there is a difference in book income and taxable income on the company's aggressive (Low ETR) and not aggressive (High ETR). The company did the aggressiveness of the tax (Low ETR) has the value relevance of information lower than the company did not do tax aggressiveness (High ETR).